2022
DOI: 10.1155/2022/2353115
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Stress-Mediated AMPK Activation Promotes GPX4-Dependent Ferroptosis through the JAK2/STAT3/P53 Axis in Renal Cancer

Abstract: Energy stress is an unfavorable condition that tumor cells are often exposed to. Ferroptosis is considered an emerging target for tumor therapy. However, the role of ferroptosis in energy stress in renal cancer is currently unknown. In this study, we found that glucose deprivation significantly enhanced GPX4-dependent ferroptosis through AMPK activation. Further, AMPK activation suppressed GPX4 expression at the transcriptional level through the upregulation of P53 expression. Additionally, the inactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…When activated, AMPK inhibited JAK2 and STAT3 phosphorylation, increased p53 expression, and decreased GPX4 expression, thereby contributing to the promotion of ferroptosis in renal cancer. 32 The activated JAK2/STAT3 pathway induces TGF-β1 secretion from tumor-associated macrophages (TAMs), which in turn activates HLF-GGT1 axis and ultimately contributes to ferroptosis resistance, proliferation, metastasis, and chemotherapy resistance of TNBC cells. 33 FANCD2 acted as a tumor suppressor by reducing JAK2 and STAT3 phosphorylation, hindering osteosarcoma cell proliferation and inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When activated, AMPK inhibited JAK2 and STAT3 phosphorylation, increased p53 expression, and decreased GPX4 expression, thereby contributing to the promotion of ferroptosis in renal cancer. 32 The activated JAK2/STAT3 pathway induces TGF-β1 secretion from tumor-associated macrophages (TAMs), which in turn activates HLF-GGT1 axis and ultimately contributes to ferroptosis resistance, proliferation, metastasis, and chemotherapy resistance of TNBC cells. 33 FANCD2 acted as a tumor suppressor by reducing JAK2 and STAT3 phosphorylation, hindering osteosarcoma cell proliferation and inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2/STAT3 pathway is a signaling pathway involved in ferroptosis that has been studied more in recent years. When activated, AMPK inhibited JAK2 and STAT3 phosphorylation, increased p53 expression, and decreased GPX4 expression, thereby contributing to the promotion of ferroptosis in renal cancer 32 . The activated JAK2/STAT3 pathway induces TGF‐β1 secretion from tumor‐associated macrophages (TAMs), which in turn activates HLF‐GGT1 axis and ultimately contributes to ferroptosis resistance, proliferation, metastasis, and chemotherapy resistance of TNBC cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that a GPX4-dependent cancer cell state underpins clear-cell morphology and imparts ferroptosis sensitivity [74]. Li et al [75] revealed that energy-stress-mediated AMPK activation promoted GPX4-dependent ferroptosis in renal cancer by way of the JAK2/STAT3/P53 axis. Another study demonstrated that ether lipid plasticity enhanced ferroptosis susceptibility and evasion [76].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
“…Previous studies have shown that the transcription factors such as stem cell factor (SOX2), BTB and CNC homology 1 (BACH1) play important roles in ferroptosis of cancer cells [29,30]. The signal transduction and activators of transcription 3 (STAT3)-mediated ferroptosis regulate the progression of PCa and kidney cancer [31,32]. Recently, lncRNAs have been reported to involve in heavy metals induced cancer development.…”
Section: Frlncrnas Regulates Genes Through Transcription Factors and ...mentioning
confidence: 99%